Exploring neuropedagogical principles for second-language acquisition in elementary learners - Heredia Muñoz, Paola Gabriela (2025)
This literature review was conducted using a systematic methodology to investigate the role of neuropedagogical principles in enhancing second-language acquisition for elementary students. As well as the cognitive and emotional features of neuropedagogical approaches in early childhood development and teacher perceptions. Through the use of keywords, Boolean operators and exclusion criteria, a total of 17 scientific articles were selected for analysis.  Four neuropedagogical strategies were found to encourage children to learn English as a foreign language: multisensory learning, technology and multimedia resources, Total Physical Response (TPR) and Project-Based Learning (PBL). It was concluded that neuropedagogical strategies encourage students to learn English by fostering active class participation and making vocabulary acquisition enjoyable. Neuropedagogical strategies were also effective in promoting brain plasticity and adaptability when acquiring new knowledge.